Interpretation of Islamic Law regarding Female Circumcision in Indonesia: Fatwa Analysis and Ulama Opinions - Rudi Hartono; Wulan Febriani (Indonesian Journal of Islamic Law, 2020)
This study examines the interpretation of Islamic law regarding the practice of female circumcision in Indonesia, with a focus on analysis of fatwas and opinions of ulama from various schools of thought. Normative juridical methods are used to evaluate religious texts and the opinions of ulama, identifying divergences of opinion rooted in the interpretation of different schools of thought. The research results show that female circumcision, while considered obligatory by the Shafi'i school of thought , is seen as permissible by the Hanafi and Hambali schools of thought. The discussion also covers the health and social implications of this practice, highlighting the role of female circumcision in gender structures and social identities. This study contributes to a deeper understanding of the legal, health, and social dynamics surrounding female circumcision in Indonesia, and proposes policy changes that support women's rights.